Public Perception on Autonomous Vehicle in Malaysia - Mohamed Jamil, H.; Shabadin, A.; Hashim, H.H.; Poi, A.W.H.; Hamidun, R.; Roslan, A.; Abd Ghani, M.R. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Autonomous Vehicle (AV), also known as self-driving or driverless vehicles, is a technology that intends to replace driving tasks traditionally performed by human drivers. This study aims to gain a better understanding of opinions, concerns, and general acceptance by Malaysian drivers regarding autonomous and self-driving vehicles. The survey questionnaires were adopted from Schoettle & Sivak (2014b) on the topic of public acceptance of driverless vehicles and what would the respondents do when they are not driving. The survey was conducted among the general public in Malaysia inclusive of 19 questions to address topics on public awareness and understanding about AV, benefits of AV, concerns on AV, attitudes toward owning or sharing AV, willingness to pay for AV and their use of free time while riding AV. A total of 520 respondents involved in this survey, however the analysis only considered the respondents who have heard of AV, which amounted to 361 via face to face interview and online survey form. Based on the survey,63.7% were male and 36.3% female. Only 15.2% of the respondents said that they would not ride in a completely self-driving vehicles. AV is also expected to provide a wide range of benefits that attracted most of the respondents. The majority of the respondents expect lower vehicle emission and better fuel economy. Most respondents were also concerned with issues related to AV especially on safety consequences of equipment failure. The survey also shows that most Malaysians are not willing to invest in owning a driverless vehicle. Future studies should continuously consider people’s perception from different perspectives, by taking into account various user viewpoints and characteristics.